Apparent digestibility coefficients of feed ingredients and essential amino acid requirements of dusky kob (Argyrosomus japonicus) - Adesola, Abidemi Adejoke (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2017)
Important to the evaluation of potential feed ingredients for inclusion in fish diets should be their digestibility and amino acid requirement so that feeds can be formulated on a digestible basis rather than a gross nutrient basis. This thesis established techniques for faecal collection, the validity of digestibility markers, it determined apparent digestibility coefficients for various novel feed ingredients, and it established the optimal lysine requirement for Argyrosomus japonicus, which was used to estimate each of the essential amino acid requirements by using the ideal protein concept. There were no significant differences in dry matter apparent digestibility coefficients when faeces were collected by stripping (77.0 %), dissection (80.1 %) or settlement (83.5 %). Faecal collection by the settlement method produced the most reliable digestibility data. Apparent digestibility coefficients for dry matter, crude protein and energy calculated using acid-insoluble ash were higher (84.0 %, 93.2 % and 93.0 %, respectively) than those using chromic oxide (55.7 %, 79.1 % and 78.2 %) and titanium dioxide (58.6 %, 79.7 % and 80.5 %). The magnitude of variation in digestibility coefficients obtained using acid-insoluble ash was always lower than that obtained with the other markers. Therefore, acid-insoluble ash was preferred as a dietary marker. Using the above protocol, protein and amino acid digestibility of some animal and plant protein ingredients were evaluated in a series of experiments. The first trial compared the apparent digestibility coefficients of some animal products included as single protein source in the test diets. Apparent protein digestibility values were 84.5 %, 83.8 %, 85.8 % and 83.1 % for fishmeal-prime, fishmeal-standard, poultry meal and pork meal, respectively. Apparent digestibility coefficients for poultry meal were comparable to those of fishmeal, which indicate its potential as a substitute for fishmeal in the diets of A. japonicus. The second trial determined the apparent coefficients of plant and animal protein sources included at 30 % into a practical reference diet (70 %). Apparent protein digestibility ranged from 92.4 % in sunflower meal to 85.5 % in corn gluten meal. Soybean meal is a promising feed ingredient in A. japonicus due to the high apparent digestibility of its protein (92.0 %) and essential amino acid digestibility (mean average 91.4 %). A fundamental assumption in fish feed formulation is that the digestibility of nutrients is additive, i.e., digestibility of a nutrient in one ingredient does not interact with the digestibility of the same nutrient in another ingredient. In the third trial, additivity of feed ingredients was tested using pork meal and poultry meal. The results indicate that the apparent digestibility coefficient of animal protein ingredients could be calculated from compound diets to accurately determine protein and amino acid digestibility in A. japonicus, and possibly other carnivorous fish species. Dietary essential amino acid requirements were determined for juvenile A. japonicus in two trials. A dose-response study was conducted using crystalline lysine to determine the optimal requirement of dietary lysine for A. japonicus. Optimal dietary lysine was estimated at 31.7 g kg-¹ dry diet, corresponding to 73.5 g kg-¹ of dietary protein, based on specific growth rate and broken-line segmented regression analyses. Dietary requirements for other essential amino acids ranged from 22 g kg-¹ (histidine) to 71 g kg-¹ (leucine) crude protein. The results of the present study provided a research tool that could be used to assess and verify the conclusions of earlier dietary work on A. japonicus and in further studies to develop least cost diet formulations for this species. The study also adds to the knowledge of the nutritional requirements of A. japonicus by providing information on the digestibility of plants and animal protein ingredients. It also contributes to future dietary research for this species because this study determines, for the first time, the most suitable methods for investigating the digestibility of raw materials for A. japonicus.
Keywords: Amino acids in animal nutrition; Fishes -- Feeding and feeds; Argyrosomus japonicus; Argyrosomus; Argyrosomus japonicus -- Nutrition; Argyrosomus -- Nutrition; Argyrosomus japonicus -- Feeding and feeds; Argyrosomus -- Feeding and feeds